A Black Odyssey John Lewis Waller and the Promise of American Life, 1878 -1900 - Woods, Randall Bennett (University Press of Kansas, 1981)
This book focuses on the career of a single individual-an ambitious, resourceful Black American-and his efforts to realize personal fulfillment in a racist world.No Black American was more determined to realize the promise of American life following the Civil War, nor more frustrated by his inability to do so than John Lewis Waller. Waller, whose first twelve years were spent in slavery, overcame his humble beginnings to become a politician, lawyer, journalist, and diplomat. Nevertheless, his life provides a case study of a middle class black caught between a desire to work within the existing political and economic framework and a need to reject a milieu that was becoming increasingly racist.Waller spent his childhood as a slave in Missouri, and his adolescence on a farm in Iowa. Circumstances and personal ambition combined to allow Waller to acquire a trade-barbering-and a profession-lawyering-in the 1870s. In 1878 he migrated to frontier Kansas, where he practiced law, edited a newspaper, rose to a position of leadership in the black community, and became an important figure in the state Republican party. His political career ended abruptly in 1890, however, when the Republicans rejected his bid to be nominated as the party's candidate for state auditor. Convinced that his defeat was due to the rising tide of racism throughout the nation, he turned his attentions abroad.Waller was particularly susceptible to the lure of overseas empire because he had spent much of his adult life in the midst of a community of people who had succumbed to the myth of a "promised land," who were convinced that the Black person would be best able to realize his potential in economically underdeveloped regions not yet exploited and controlled by the white man. In 1891 President Benjamin Harrison appointed Waller United States consul to the east African island of Madagascar. By 1894 Waller had obtained a huge land grant there for the founding of a black utopia. He hoped to establish a plantationcolony that would simultaneously advance his personal fortunes, serve as an investment opportunity for aspiring black capitalists, and constitute a refuge for oppressed AfroAmericans who wished to immigrate. He was thwarted once again by racism, however-this time in the guise of French imperialism. Viewing Waller and his plans as a threat to their hegemony in Madagascar, French authorities quashed the concession, arrested Waller on a charge of being a spy, and sentenced him to twenty years in prison. There followed a fullscale diplomatic confrontation between the United States and France. Waller was released after serving ten months in a French prison, but only after the Cleveland administration agreed to discredit him to the point where he would seem guilty as charged.In his early manhood John Lewis Waller had realized that because he was a Negro personal achievement could not be separated from racial advancement. Responding to that perception, he spent a lifetime searching for a frontier where blacks could enjoy the blessings of democracy and capitalism, and yet be free of the blight of racism. Unlike the vast majority of American Blacks of his time, Waller was able to articulate his dreams, have an impact on the larger, white dominated environment, and realize his individual potential to a remarkable degree. Nevertheless, his dreams were ultimately dashed by racism. His sad but fascinating story deserves the careful attention of all students of politics and race relations during the complex postCivil War year.